2019
DOI: 10.3747/pdi.2018.00169
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in Peritoneal Dialysis Patients

Abstract: Constipation in peritoneal dialysis (PD) is an infrequent but potentially serious condition affecting the mechanical properties of dialysis techniques and predisposing to bacterial intestinal translocation and eventual enteric peritonitis. Despite the importance of the problem, published literature is scarce, consisting mostly of uncontrolled single-center trials. This inconsistency may be attributed to the large number of clinical, radiological, and endoscopic tools that have been used in the studies with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…27 In particular, among patients with CKD who are typically characterized by an immense burden of medications, comorbidities, and metabolic abnormalities, 62 the cause of constipation is highly multifactorial, involving many complex pathophysiological mechanisms, as summarized in Figure 2. 1,5,[63][64][65][66][67][68][69][70][71][72][73][74][75][76] Although there is a lack of consensus in the published literature, most of these predisposing factors (listed in Figure 2) appear to be shared by the general population. With a few notable exceptions, the strict dietary restrictions (e.g., low-fiber diets [to avoid hyperkalemia] and limited fluid intake [to avoid volume overload]), frequent use of constipation-inducing medications (e.g., phosphate binders, potassiumlowering agents, calcium channel blockers, opioids, iron supplements, and antidepressants), uremic toxins, and altered gut microbiota, all of which are typically present in patients with CKD, may further contribute to increase the prevalence of constipation in this particular population.…”
Section: Pathophysiology and Etiology Of Constipation In Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…27 In particular, among patients with CKD who are typically characterized by an immense burden of medications, comorbidities, and metabolic abnormalities, 62 the cause of constipation is highly multifactorial, involving many complex pathophysiological mechanisms, as summarized in Figure 2. 1,5,[63][64][65][66][67][68][69][70][71][72][73][74][75][76] Although there is a lack of consensus in the published literature, most of these predisposing factors (listed in Figure 2) appear to be shared by the general population. With a few notable exceptions, the strict dietary restrictions (e.g., low-fiber diets [to avoid hyperkalemia] and limited fluid intake [to avoid volume overload]), frequent use of constipation-inducing medications (e.g., phosphate binders, potassiumlowering agents, calcium channel blockers, opioids, iron supplements, and antidepressants), uremic toxins, and altered gut microbiota, all of which are typically present in patients with CKD, may further contribute to increase the prevalence of constipation in this particular population.…”
Section: Pathophysiology and Etiology Of Constipation In Ckdmentioning
confidence: 99%
“…37 Impact on Clinical Outcomes Constipation has been increasingly recognized as a potentially serious condition, particularly in patients with ESRD receiving PD, affecting the mechanical properties of dialysis techniques and predisposing to bacterial intestinal translocation and eventual enteric peritonitis. 76 Although little attention has been paid to the clinical impact of constipation beyond its gastrointestinal complications (e.g., diverticulitis, perforation, and peritonitis), 6,103,104 recent studies have disclosed its independent associations with the risk of several clinical outcomes, such as Parkinson's disease, 105 ESRD, 14 CV disease, [15][16][17][18] and mortality. 18…”
Section: Clinical Impact Of Constipation In Ckd Impact On Economy Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on PD-related peritonitis, and various risk factors, such as DM and smoking, have been implicated in peritonitis among patients on PD. [1][2][3][4][5][6][7][8][9][10][11] The ISPD has published guidelines for PD-related peritonitis. 1 In our hospital, we manage patients on PD with peritonitis as per these guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…1 Awareness and information regarding the risk factors for peritonitis in PD patients are important to prevent PD-related peritonitis; several risk factors for PD-related peritonitis, such as diabetes mellitus (DM) and smoking, have been listed in the guidelines and in other reports. [1][2][3][4][5][6][7][8][9][10][11] We have used the protocols and information in these guidelines to manage peritonitis in PD patients at our hospital. Nevertheless, in PD patients, peritonitis remains a severe problem, which requires to be addressed.…”
Section: Introductionmentioning
confidence: 99%